Contextualizing Consumer Data Protection within the Operational Principles of Banking: A Legal Inquiry - Situmeang, Ampuan; Disemadi, Hari Sutra; Marsudi, Irvan Ricardo (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
This research aims to analyze the regulatory framework for the implementation of operational principles in banking as an effort to protect consumer data in Indonesia. The research method employed is normative legal research with a legislative approach to analyze banking regulations. This study involves the analysis of secondary data. The results indicate that the regulation of the implementation of operational principles in Indonesian banking has provided legal certainty in the protection of consumer data. Banks in Indonesia are mandated to maintain the confidentiality of consumer data, enhance trust, and manage risks with caution. The research also identifies several challenges and shortcomings that need further consideration to strengthen consumer data protection. The implementation of operational principles in banking, such as the Principles of Trust, Confidentiality, Prudence, and Know Your Customer (KYC) Principles, constitutes critical steps in safeguarding consumer banking data in the digital era.